Leaf morphometry of six Podocarpaceae species from Peru: A contribution to their taxonomic identification - Ramírez Peralta, José Antonio (2025)
The present study evaluated the potential use of leaf morphometry for the taxonomic identification of six Podocarpaceae species. We collected botanical samples from 17 forests across five departments in northern, central, and southern Peru (Cajamarca, Pasco, Junín, Apurímac, and Cusco), and we also performed a multivariate comparison of leaf morphometric variables (length, width, thickness, and area). Hierarchical clustering (dendrogram analysis) successfully discriminated the species, grouping localities with the presence of the same species and identifying six clusters. A Principal Component Analysis (PCA) yielded two compo nents (PCs) that explain 96.1% of the variability of the data; PC1 (71%) is associated with leaf length, width, and area, while PC2 is explained by leaf thickness. Podocarpus celatus and Podocarpus magnifolius ex hibit wide and long leaves, Prumnopitys montana and Retrophyllum rospigliosii have small and thin leaves, and Podocarpus glomeratus and Podocarpus oleifolius have medium-sized leaves. Finally, we present a brief synopsis of the evaluated species identification keys for the evaluated species, based on leaf morphometry, distribution, conservation status, botanical illustrations, and LCDP plates.